Cross or wait? Pedestrian decision making during clearance phase at signalized intersections. (February 2018) - Zhuang, Xiangling; Wu, Changxu; Ma, Shu
Graphical abstract: Highlights: Pedestrians make dynamic decisions on crossing or not, rather than obey the signal. 79% of the pedestrians crossed 41% of the road during red light. Being young or undistracted predicts higher probability of violation. Pedestrian crossed when the required speed is much higher than actual speed. A new design of pedestrian signal for the clearance phase is proposed. Abstract: Pedestrians arriving at clearance phase (Flashing Don't Walk ) face different levels of risk depending on behavioral choice afterwards. However, few studies have focused on the choices pedestrians make during this phase. This field study analyzed pedestrian choices after arrival, evaluated safety of the choices, and built a model to identify the predictors of pedestrian choices. It was found that pedestrians arriving during clearance phase made dynamic decisions based on the changing contexts. Specifically, the majority made the decision to "cross" as opposed to "wait" (85.2% vs. 14.8% respectively), although only the latter choice is legal. Seventy-nine percent of the pedestrians did not finish crossing the intersection before the traffic light turned red, and they walked 41% of the road width during a red light. For those waited, roughly half of them waited until green or crossed at an intersecting crosswalk, while others finally started on red light. Nevertheless, the waited pedestrians still faced lower risk than those crossed prematurely in terms of running behaviors, and conflicts with vehicles. Pedestrians are more likely to cross immediately after arrival when they are younger, are not engaged in secondary tasks, arrived at a position farther from approaching vehicles at the near side of the road, or arrived at a time when there are more pedestrians crossing the road. Although fewer pedestrians choose to cross when the required speed is higher (due to a wider road or less remaining time), the required speed they choose to cross at is far higher than their actual speed. These findings are essential for realistic pedestrian simulations and targeted safety countermeasures. They also imply the need for changes to certain traffic regulations and signal design to facilitate safe decision making at clearance phase.